Chronic kidney disease in type 2 diabetes: introduction - Thomas, Merlin (Henry Stewart Talks, 2023)
Diabetic Kidney Disease (DKD), Chronic kidney disease (CKD) in diabetes, Glomerular filtration, Albumin to creatinine ratio (ACR), Global burden of CKD, Risk factors for CKD in diabetes, Brenner Hypothesis, Oxygenation of the kidney in diabetes